Numerical modelling of a composite pentamode comprising a shear-thickening fluid. (2018) - Cecchini, Federico; Cherubini, Valeria; Fabbrocino, Francesco; Nanni, Francesca
In this work, we developed a novel numerical approach to the analysis of the displacement field of a Composite pentamode metamaterial. Two different approaches to the solution of the system of equations are taken into account: the first is an exact iterative approach, the second is a discrete one based on finite element modelling (FEM). The single beam elements that materialise the composite pentamode are hollow and comprise a Non-Newtonian fluid (NNF) Core. In particular, shear-thickening fluids (STFs) were selected as the materials for the core, as they are capable of converting into heat a large quantity of the kinetic energy deriving from the dynamic forces applied to the structure. In order to study the viscoelastic properties of the material considered, a two-step rheological analysis was carried out. Finally, the previous equations were solved and the results obtained for the various methods were compared.